An Evaluation of Secondary School Students’ Use and Understanding of Learning Strategies to Study and Revise for Science Examinations - Fatema Sultana; Richard C. Watkins; Tarek Al Baghal; John Carl Hughes (Education Sciences)
There is currently no population-based data evaluating secondary school-aged students’ use, or understanding of, learning strategies to study/revise independently for science. There is also no research evaluating the effort students make towards independent science study and revision, nor how schools support students with study and/or revision strategies for science examinations. In this paper, we report data from a representative sample of 385 students (aged 14 to 15 years) from 29 secondary schools in the UK, using the Effective Revision and Study Strategies Questionnaire (ERaSSQ) survey. We conducted a cross-sectional survey using a multistage implicitly stratified sampling method. Our results show that the learning strategies most frequently used by students for independent science study and revision were making notes, repeatedly reading information, and highlighting or underlining information (i.e., lower utility learning strategies). Our findings also suggest many students do not have a complete understanding of the strategies that are known to have higher utility (i.e., retrieval and spaced practice). These results represent the first attempt to gather information using robust survey methods and are of interest to secondary school science teachers and education policymakers.